Utilization of Insecticide Treated Bed Nets (ITNs) among Caregivers of Children under Five Years in the Ho Municipality - Diema Konlan, Kennedy; Japiong, Milipaak; Dodam Konlan, Kennedy; Afaya, Agani; Salia, Solomon Mohammed; Kombat, Joseph M. (Interdisciplinary Perspectives on Infectious Diseases, 2019)
Background. In Ghana, attempts to control malaria through antimalarial medications are currently threatened by the emergence and spread of drug resistant malaria parasites. This, together with the increasing incidence of malaria, has heightened the need for a more effective method of controlling the spread. The use of Insecticide Treated Bed Net (ITN) has been recognised as an effective measure in the prevention of malaria. Objective/Purpose. In this study, we examined the utilisation of ITN among caregivers of children under five years in Ho municipality of Ghana. Methods. This descriptive cross-sectional study recruited 283 household representatives through a multistage sampling method. A questionnaire was used to collect the data and was analyzed using STATA version 14. Descriptive and inferential statistics were adopted in presenting the data. Results. Ownership of ITN was higher (80.7%) than its utilisation (41.7%). The age of caregiver was strongly associated with the utilisation of ITN (AOR=2.00, 95% CI=0.00, 0.02, p<0.001) among children less than five years. Caregivers aged 26-35 were 49% times less likely to use an ITN as compared to those aged between 17 and 25 and the difference was statistically significant. Conclusion. In order to ensure a high ITN coverage and utilisation, there is the need for continuous distribution of ITNs to households. Households should be sensitized to use the nets to prevent the continuous spread of malaria.